ELEMENTS OF OPTOELECTRONICS IN THE COURSE OF GENERAL PHYSICS - Mirzaakhmad Kurbanov, Shokhida Sodikova, Khayotjon Kurbanov, Shokhida Pazilova (International Journal of Advanced Science and Technology, 2020)
This paper presents information on fiber optic fibers as a medium for the propagation of an optical signal.The conditions for the propagation of optical information through optical fiber, structures, and materials are considered. Information is given on the purpose and design of the components of the optical paths.When presenting the material, students' knowledge of the basic principles of the physics of semiconductors and semiconductor devices, sections of geometric and wave optics was taken into account.